The validity of Career Readiness Module-Cognitive Information Processing (CRM-CIP) - Mahmud, Mohd Izwan; Noah, Sidek Mohd; Ahmad, Jamaludin; Jaafar, Wan Marzuki Wan (Finlogy Publication, 2017)
The career development of university students is a transition process from education to career that needs them to be ready to plan, explore, make choices and make career decisions appropriate with one’s interest, talent and ability. Thus, the Career Readiness Module-Cognitive Information Processing (CRM-CIP) was developed as an intervention aimed to increase the students’ career readiness. This research aim to analysis the content validity of CRM-CIP. The content validity analysis used the expert consensus evaluation that consisted of eight experts. The research findings showed that the value of content validity coefficient was .955 and based on the sub modules and activities was 934. This proves that the CRM-CIP has high content validity and therefore is suitable to be implemented on the university students that have low or moderate level of career readiness.